Low-dose oral contraceptive-induced acute myocardial infarction. (1st November 2016) - Aslan, Abdullah Nabi; Süygün, Hakan; Sivri, Serkan; Keleş, Telat
Abstract: Objectives: Since their introduction, oral contraceptives (OCs) have been associated with risk to both the venous and the arterial systems. Studies have shown that OC use is associated with a risk of venous thromboembolism, ischaemic stroke and acute myocardial infarction (MI). MI is rarely seen in patients using OCs, particularly in the absence of clinical risk factors or smoking. Case: We report a case of acute inferior MI in a 20-year-old non-smoker who had used a low-dose OC (3 mg drospirenone and 30 μg ethinyl estradiol) for 1 month. As far as we know, this is the youngest case of acute MI associated with a low-dose OC. Conclusion: Low-dose OCs may also be responsible for acute MI even in a very young female without any cardiovascular risk factors. Therefore, the clinicians should be aware of this mortal events during follow-up of the patient using OCs.